Evaluation of the technological effect of egg albumin powder as a stabilizer in a cream ice cream (@limentech, Ciencia y Tecnología Alimentaria, 2023)
Egg products have been recognized for their use in food as a study matrix and with the intention of improving the physicochemical and sensory characteristics, such as melt resistance and structural stability, of cream-based ice creams. In this study, the incorporation of powdered albumin as a stabilizer in cream-based ice cream was evaluated due to its technological and nutritional properties. Initially, the physicochemical evaluation of egg albumin and the preparation of the ice cream (premix and mix) with different concentrations of albumin were conducted, using concentrations of 50:50, 70:30, 80:20, and 100% chemical stabilizer. Each physicochemical test for the albumin was performed in triplicate, evaluating particle size, color, gelation, and water absorption index. Similarly, tests were conducted on the cream-based ice cream, such as viscosity, melting, overrun, and free fat content. A sensory analysis was carried out among the four formulations of cream-based ice cream to observe their level of acceptability, and it was analyzed using Friedman's non-parametric test to identify significant differences between the four formulations. The best performance was obtained with the 50:50 substitution, which had an 11.47% loss percentage during the ice cream processing, attributed to its water absorption capacity, a functional property of proteins. The sample that received the highest acceptance from panelists in terms of color, taste, smell, and texture was coded 987, representing the 80:20 formulation of egg albumin and xanthan gum. Finally, costs were calculated, yielding a value of $3,488 COP for an 85-gram presentation with a 100% substitution.
Keywords: Egg albumen; ice cream; texture; stability